Sex Offender Height and Pedophilic Interest: A Clarification. Issue 10 (3rd October 2019) - Levenson, Jill S.; Ackerman, Alissa R.
ABSTRACT: The authors investigated the relationship between offender height and pedophilic interest in a sample of 22, 228 registered sex offenders (RSOs). Concerns have been raised by a former collaborator that some of the data used in the analyses might be unreliable. In this clarification research note, we respond by briefly summarizing our methodology, describing the concerns, and then discussing our rationale for decisions made in the sampling procedures and analyses.